Analisis Faktor-Faktor Yang Mempengaruhi Luas Pengungkapan Sukarela Laporan Tahunan Perusahaan (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2016) - Aida Nahar; Linda Selfia Saputri (Accounting Study Program, Faculty of Economics and Business, 2017)
The voluntary disclosures that vary widely from one company to another vary. These differences can be influenced by the characteristics of the company. This study aims to analyze the effect of firm size, leverage, profitability, public share ownership, liquidity, company listing age, and KAP size on the extent of voluntary disclosure in the company's annual report. The population in this study are all manufacturing companies that have complete data and are consistently listed on the Indonesia Stock Exchange in 2014-2016. The sampling technique was carried out using the saturated sampling method. The number of samples in this study were 65 companies. The data used in this study is documentary data in the form of annual report data of manufacturing companies listed on the Indonesia Stock Exchange in 2014-2016. The data analysis method used is multiple linear regression analysis. The results of this study indicate that company size and public share ownership have a positive effect on the extent of voluntary disclosure in the company's annual report. Meanwhile, leverage, profitability, liquidity, company listing age, and KAP size have no effect on the extent of voluntary disclosure in the company's annual report.